Incidental Finding of a Rare Urachal Pathology: Urachal Mucinous Cystic Tumour of Low Malignant Potential. (3rd January 2016) - Wang, Luke L.; Liddell, Heath; Tanny, Sharman Tan; Norris, Briony; Appu, Sree; Pan, David
Abstract : Urachal mucinous cystic tumours are rare pathological findings with only 23 previously reported cases in the literature. We present the case of a 54-year-old man with an incidentally found urachal mucinous cystic tumour laparoscopically excised. With its known potential to cause pseudomyxoma peritonei, complete surgical excision is important. Long-term cystoscopic and radiological surveillance is also required.